Implementation of Science Practical Work at Faculty of Teacher Training and Educational Science, Universitas Terbuka, Indonesia - Amalia Sapriati; Ucu Rahayu; Yoyoh Kurniawati (Bandar Lampung University (UBL), 2013)
Science practical work is an important part of Biology Teacher Education Program (BTEP) curriculum in order to (1) show confirmation and illustration of theory, and (2) develop students’ knowledge and skills to teach successfully in junior and senior high school science laboratory. This paper describes how UT conducts the practical work and how student’s perception toward the implementation of practical work. The paper was based upon the study of the practical work implementation in the first semester of 2011, at an UT-Regional Office (RO). Data were collected by interviewing practical work instructors, distributing a questionnaire to 15 students, and observing practical work activity. The results of the study revealed that (1) UT/RO collaborated with a face to face institution of higher education to facilitate BTEP students doing practical work activity, (2) the students actively participated to accomplish the required tasks of practical works and wrote the report, (3) practical work assessment was based upon students’ performance and practical work report, and (4) students considered that practical work will develop their understanding of scientific concepts, science skills, curiosity, and ability to work carefully and systematically. The conclusion of the study were (1) implementation of practical work tended to be used for confirmation and illustration theory and presentation experience for future teaching, and (2) students well and actively performed the practical work, were capable to write the report, and revealed positive perception toward the practical work.